Collaborative Governance of Religious Tolerance Policy and Its Role in Sustaining Tourism Development in Priority Destinations: Evidence from Lombok Tengah, Indonesia - Zakaria Ansori; Agus (Politea : Jurnal Politik Islam, 2026)
Sustainable tourism in Indonesia's priority destinations presupposes a socially enabling environment in which communities can accommodate the diversity of incoming visitors. Religious tolerance as a collective social disposition shaping inter-group openness constitutes a foundational dimension of this enabling environment. Yet most existing scholarship treats tolerance governance either as an educational matter or as a straightforward administrative function of the central state, leaving unexplored the multi-actor, sub-national governance dynamics that actually determine tolerance outcomes at the community level. This study examines the religious tolerance index among communities in Lombok Tengah Regency Indonesia's nationally designated Special Economic Zone (SEZ) for tourism within the Mandalika development corridor and proposes a collaborative governance model capable of sustaining and deepening religious tolerance alongside the regency's accelerating tourism expansion. A sequential explanatory mixed-methods design was employed. Quantitative data were gathered through a structured survey instrument (n = 348) measuring four empirical dimensions: public perception, attitude, social cooperation, and government disposition, operationalised on a 1–4 Likert scale. Qualitative data derived from twenty-three semi-structured, in-depth interviews with district-level government officials, Ministry of Religious Affairs officers, FKUB members, religious leaders from three faith traditions, civil society representatives, and regional planning bureaucrats, supplemented by participant observation at three inter-faith dialogue events and systematic document analysis. The composite tolerance index stands at 3.61 (on a 1–4 scale; category: High). Internal variance is notable: government disposition scores highest (3.93) while attitude (3.10) and social cooperation (3.16) remain at moderate levels, indicating a gap between normative endorsement and lived inter-religious practice. Educational attainment, age cohort, and sex significantly predict individual tolerance behaviour. Qualitative analysis identifies four structural constraints on governance: electoral majority-pandering incentives, inconsistent moderation leadership, a homogeneous social-religious ecology, and an underdeveloped public sphere for inter-faith exchange. The prevailing institutional arrangement is a triple-helix collaboration government, FKUB, and religious organisations operating under a regulatory framework that has not been updated to incorporate the 2023 Presidential Regulation on Religious Moderation. The study proposes a hexa-helix collaborative governance model incorporating government, FKUB, civil society and religious organisations, the private sector, mass media, and higher education institutions. This model addresses the structural constraints identified empirically and aligns with the legislative architecture of Perpres No. 58/2023 and PMA No. 3/2024. It re-centres tolerance governance as a multi-stakeholder ecosystem rather than a unilateral bureaucratic function, directly supporting Lombok Tengah's sustainable tourism trajectory under the RPJPD 2025–2045